Folk Poetic Rhetoricity in Ḍeuḍā Performance - Air, Narendra Bahadur (Medha: A Multidisciplinary Journal, 2025)
This study investigates the folk poetic rhetoricity of Ḍeuḍā, a popular oral performance tradition of the Sudurpaschim and Karnali regions of Nepal. The primary aim is to examine how Ḍeuḍā functions as a rhetorical art that entertains, educates, and persuades audiences within communal contexts. The research applies rhetorical theories of Aristotle, Kenneth Burke, and other scholars to analyze Ḍeuḍā songs collected from live performances and published sources. The analysis reveals that Ḍeuḍā employs a wide range of rhetorical devices including metaphor, imagery, satire, irony, wit, repetition, defense, and artistic invocation. Performers make use of both artistic proofs, such as ethos, pathos, and logos, and inartistic proofs, such as anecdotes, folk images, and local examples, to influence attitudes and actions. The dialogic and competitive nature of duet and group performances further amplifies the rhetorical force, allowing singers to address sensitive issues of caste, gender, politics, morality, and love in symbolic and often satirical ways. Findings suggest that even though most Ḍeuḍā poets are non-literate, they demonstrate rhetorical ingenuity, intellectual versatility, and mastery of vernacular languages. Their performances generate cathartic, aesthetic, and ethical effects by blending poetry, music, and dance. In conclusion, Ḍeuḍā emerges as more than a folk literary form; it is a dynamic rhetorical practice that communicates vernacular knowledge, critiques social evils, and strengthens cultural identity. The study highlights its enduring significance as a medium of persuasion where folk poetics and performance converge to shape communal consciousness.